2011
DOI: 10.1111/j.1439-0531.2011.01802.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritionally Induced Relationships Between Insulin Levels During the Weaning‐to‐Ovulation Interval and Reproductive Characteristics in Multiparous Sows: II. Luteal Development, Progesterone and Conceptus Development and Uniformity1

Abstract: Insulin-stimulating sow diets before mating improve piglet uniformity. We studied effects of nutritionally induced differences in insulin levels during the weaning-to-ovulation interval (WOI) on luteal development, progesterone secretion and pre-implantation conceptus development and uniformity (d10). To create insulin contrasts, 32 multiparous sows were fed either a dextrose plus lactose containing diet (each 150 g/day) at 4 h intervals (DL treatment) or an isocalorically control diet (containing soybean oil)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 27 publications
2
29
1
Order By: Relevance
“…Increased levels of FSH during the follicular phase increase follicular size [39,40] and the size of the CL [38,41], which lead to elevated P4 levels [42].…”
Section: Paritymentioning
confidence: 99%
See 1 more Smart Citation
“…Increased levels of FSH during the follicular phase increase follicular size [39,40] and the size of the CL [38,41], which lead to elevated P4 levels [42].…”
Section: Paritymentioning
confidence: 99%
“…Wientjes et al [42] reported that there is a positive relationship between follicle size and the size and weight of the CL, indicating that larger follicles develop into larger CL, which then produce more P4. Although treatment with peforelin increased follicle diameter in this work, this did not significantly increase P4 levels.…”
Section: Paritymentioning
confidence: 99%
“…Higher piglet birth weights and litter uniformity have been found using insulin-stimulating sow diets before mating (Van den Brand et al, 2006 and2009), probably through beneficial effects of insulin and/or IGF-1 on follicle development (as reviewed by Quesnel, 2009). In a previous study, we found positive relationships between premating insulin concentrations and luteinizing hormone (LH), follicle development and subsequent progesterone concentrations (luteal development) and embryo size (but not uniformity) at day 10 of pregnancy (Wientjes et al, 2012b and2012c). Whether and how these effects lead to a more -E-mail: nicoline.soede@wur.nl uniform development of fetuses at later stages of pregnancy, however, needs further study.…”
Section: Introductionmentioning
confidence: 96%
“…In fact, the study of Almeida et al (2001) showed a more rapid raise in progesterone after ovulation in feed-restricted gilts treated with exogenous insulin, suggesting that insulin treatment affected the luteinizing process, and hence the production of progesterone in the immediate postovulatory period. Further evidence has been recently reported by Wientjes et al (2012c) in sows, by demonstrating that an increased total luteal weight, as a result of either a higher ovulation rate or larger individual corpora lutea or both, seems to be beneficial for progesterone production and secretion. Therefore, premating insulin-stimulating diets may improve embryo survival, and the beneficial effects of premating insulinstimulating diets on embryo survival may be driven by progesterone levels, as reported by Wientjes et al (2012c), as plasma progesterone levels during early pregnancy are related to embryo survival (Jindal et al, 1996(Jindal et al, , 1997Almeida et al, 2000).…”
Section: Discussionmentioning
confidence: 66%
“…Further evidence has been recently reported by Wientjes et al (2012c) in sows, by demonstrating that an increased total luteal weight, as a result of either a higher ovulation rate or larger individual corpora lutea or both, seems to be beneficial for progesterone production and secretion. Therefore, premating insulin-stimulating diets may improve embryo survival, and the beneficial effects of premating insulinstimulating diets on embryo survival may be driven by progesterone levels, as reported by Wientjes et al (2012c), as plasma progesterone levels during early pregnancy are related to embryo survival (Jindal et al, 1996(Jindal et al, , 1997Almeida et al, 2000). On the other hand, the present results indicate that dietary-induced insulin enhancement during the late luteal phase does not seem to mediate effects on embryonic survival to day 28 of pregnancy, as the development of day 28 conceptuses is related to the extent of embryonic loss during the first 4 weeks of pregnancy (Lutter et al, 1981).…”
Section: Discussionmentioning
confidence: 66%